Left ventricular dysfunction in Duchenne muscular dystrophy. (22nd January 2020) - James, Katherine A.; Gralla, Jane; Ridall, Leslie A.; Do, ThuyQuynh N.; Czaja, Angela S.; Mourani, Peter M.; Ciafaloni, Emma; Cunniff, Christopher; Donnelly, Jennifer; Oleszek, Joyce; Pandya, Shree; Price, Elinora; et al.
Abstract: Background: Duchenne muscular dystrophy is associated with progressive cardiorespiratory failure, including left ventricular dysfunction. Methods and Results: Males with probable or definite diagnosis of Duchenne muscular dystrophy, diagnosed between 1 January, 1982 and 31 December, 2011, were identified from the Muscular Dystrophy Surveillance Tracking and Research Network database. Two non-mutually exclusive groups were created: patients with ≥2 echocardiograms and non-invasive positive pressure ventilation-compliant patients with ≥1 recorded ejection fraction. Quantitative left ventricular dysfunction was defined as an ejection fraction <55%. Qualitative dysfunction was defined as mild, moderate, or severe. Progression of quantitative left ventricular dysfunction was modelled as a continuous time-varying outcome. Change in qualitative left ventricle function was assessed by the percentage of patients within each category at each age. Forty-one percent (n = 403) had ≥2 ejection fractions containing 998 qualitative assessments with a mean age at first echo of 10.8 ± 4.6 years, with an average first ejection fraction of 63.1 ± 12.6%. Mean age at first echo with an ejection fraction <55 was 15.2 ± 3.9 years. Thirty-five percent (140/403) were non-invasive positive pressure ventilation-compliant and had ejection fraction information. The estimated rate of decline in ejection fraction from first ejection fraction was 1.6% per year and initiation of non-invasive positive pressure ventilation did not change this rate. Conclusions: In our cohort, we observed that left ventricle function in patients with Duchenne muscular dystrophy declined over time, independent of non-invasive positive pressure ventilation use. Future studies are needed to examine the impact of respiratory support on cardiac function.